India's Vision of a Healthy and Developed Nation: An Analysis of the Perspective of Healthtech Industry - Hood, Mitesh Mohan; Kapoor, Vaibhav; Sawhney, Garima; Singh, Harsimarbir (New Advances in Business, Management and Economics Vol. 5, 2025)
Background: India's vision of becoming a healthy and developed nation by 2047, marking 100 years of independence, is a significant national objective. The healthtech industry, encircling pharmaceutical innovations, medical devices, biotech and digital health, plays a significant part in this transformational journey. Purpose: India's aspiration to become a developed and healthy nation by 2047 is intrinsically tied to advancements in the healthcare technology (healthtech) industry. This article evaluates the role of health technology in transforming healthcare delivery, improving health outcomes, and driving economic growth. It also examines the current state of the healthtech industry in India, identifying key challenges, opportunities, and strategic initiatives required for achieving this vision. Methods: The study involved a comprehensive review of recent reports and literature on the healthtech sector in India. Data was analyzed from various sources including market reports, government initiatives, and industry publications to assess the current landscape, growth projections, and sector-specific developments. Results: In 2024, the Indian healthtech market was valued at $6.5 billion, with projections indicating significant growth to approximately $78.4 billion by 2033, reflecting a CAGR of 28.67%. Key sectors such as digital health, medical devices, biotech, and pharmaceuticals are evolving rapidly. However, challenges such as inadequate infrastructure, regulatory hurdles, and a shortage of skilled professionals persist. Opportunities include expanding digital health infrastructure and fostering public-private partnerships. Funding mechanisms, such as research grants, innovation challenges, and tax incentives, can incentivize researchers and startups to develop novel solutions. Additionally, creating innovation subsidies for research in health technology can foster a culture of innovation and drive the translation of research into practical applications. Conclusions: The healthtech industry is crucial for realizing India’s vision of improved health and development. Addressing existing challenges and leveraging opportunities through strategic initiatives and collaborations will be essential. The convergence of technology and healthcare has the potential to revolutionize healthcare delivery, enhance patient outcomes, and support national development goals. Strategic initiatives and a collaborative approach will be key to achieving this ambitious vision. The convergence of technology and healthcare has the potential to revolutionize healthcare delivery, empower patients, and create a more equitable and sustainable healthcare ecosystem.